Dampak Tayangan Sinetron Azab Orang Ketiga Di Indosiar Bagi Ibu Rumah Tangga Desa Karang Anyar Kecamatan Aek Kou Kabupaten Labuhan Batu Utara Provinsi Sumatera Utara - Citra Hasanah; Dedi Sahputra; Ressi Dwiana (Universitas Medan Area, 2022)
The research entitled The Impact of Third Person Azab soap operas in Indosiar (a case study on housewives in Karang Anyar Village, Aek kuo District, Labuhan Batu Utara Regency, North Sumatra Province). This study aims to see the impact of what happens in the household, especially for housewives after watching the soap opera The Third Person in Indoosiar. The sensation of housewives regarding the soap opera The Third Person in Indosiar became the main spotlight because they felt something unique when watching the soap opera, from feeling annoyed, sad, funny, to feeling nothing. According to the Indonesian Broadcasting Commission (KPI), this program series received the highest rating of 1.7 points compared to the ratings of other shows. This soap opera which airs at 11.30 WIB is a soap opera that is in great demand by housewives aged 29-46 years. The results of the interview showed that the result of watching the soap opera The Third Person's Azab had both positive and negative impacts. One of the positive impacts that occurs is providing education and teaching that taking what is not ours must be rewarded, as entertainment in free time. A negative impact began to occur in a lack of focus on traders which resulted in losses to their merchandise, causing losses because they always played the broadcast, raising suspicion towards her husband who worked outside the region. The hope for housewives regarding the soap opera The Third Person in Indosiar is that they hope that the soap opera with the theme of religion is not too excessive. The method used in this research is descriptive - qualitative, which uses interviews with several sources. While the data informant techniques used in this study were in-depth interviews, documentation, internet searches, and research informants. The conclusion of this study is that various kinds of attitudes and behavior of housewives ranging from good to bad are acceptable because each individual has different perspectives and perceptions and deserves our respect.